RESPON KEPUASAN PASIEN PENGGUNA BPJS KESEHATAN TERHADAP PELAYANAN KESEHATAN DIPUSKESMAS PEKANBARU - Ayu Septia Ningrum; M. Razif " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
PHC, is a functional organization that organizes health effort that is comprehensive, integrated, equitable, acceptable and affordable by the community, with the active participation of the community and use the results of the development of science and appropriate technology, at a cost that can be borne by the government and society. service is an activity or sequence of events that occur in the interaction between a person directly or with another person or machine physically and provide customer satisfaction. Happens in the health center services Rejosari for patients who visit many expressed good and satisfying service. Although there are some who declare less good service. The theory used is the theory of perception. Perception can be defined as the process of organizing sitimulus received by the individual senses, then interpreted so that individuals are aware of and understand about what is acceptable to the senses. Perception is an integrated state of the person who receives the stimulus, then what is in a person, the experiences will participate actively in these perceptions. The method used is descriptive quantitative, then the respondent by means anyone who inadvertently meet with researchers and investigators in accordance with the characteristics specified then that person can be used as respondents. Teknnik collecting data used were observation and interviews.Keywords: health centers, Care, Perception